FUNCTIONAL PROPERTIES OF CATFISH SKIN COLLAGEN HYDROLYSATES - Ayat, A. A.; Shakir, K. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Collagen hydrolysates were obtained from catfish skin collagen hydrolysis using catfish collagenase, pepsin and trypsin individually and mixed for 15-300min. The degree of hydrolysis , antioxidant activity based on, DPPH radical-scavenging activity (RSA), and reducing power (RP) for all obtained hydro lysates were studied , then the collagenase hydrolysate was (CH)  was selected to be evaluated for  antibacterial activity , functional properties including solubility, emulsification and foaming  properties besides the toxicity  . The highest values for RSA (72.5%) has been noticed when DH reached (24.30%) after 30 min. of hydrolysis by collagenase (CH). The water and oil holding capacities for this hydro lysate was compared to that for ASC (acid soluble collagen and PSC (pepsin soluble collagen), the results showed that the values recorded by CH were significantly higher than ASC & PSC. The molecular weight of CH peptides ranged from 180 to 11 Da. as analyzed by SDS- PAGE.  The toxicity assay result revealed that CH is safe for human consumption. There was no antibacterial function for CH toward E.coli and S. aureus. At concentration of 2mg/ml. This study suggests that catfish collagen hydro lysate could be a good natural alternative for synthetic antioxidants in food industries.